Feasibility Study of Nickel Mixed Hydroxide Precipitate (MHP) Smelter Construction Plan with High Pressure Acid Leaching (HPAL) Technology - Santika, Dewi; Oetomo, Dedy Setyo; Yudha , Haris Sandi (Yayasan Gema Bina Nusantara, 2025)
This study evaluates the feasibility of building a nickel Mixed Hydroxide Precipitate (MHP) plant of PT. X with a capacity of 12,000 tons per year. The analysis shows that the potential demand for MHPs in the national and global markets continues to increase, driven by the growth of the nickel battery-based electric vehicle industry. The planned production capacity is projected to be optimally absorbed. The plant is designed using High Pressure Acid Leaching (HPAL) technology that utilizes low-grade nickel ore from multiple locations to reduce dependence on a single mine. Other supporting factors include adequate infrastructure, manpower, regulatory support, and market potential. Raw material requirements per year include 414,000 tons of laterite ore, 148,100 tons of H₂SO₄, 41,700 tons of CaO, and 2,870 tons of MgO. Initial investment (CAPEX) is estimated at 108.8 million with an annual operating expense (OPEX) of 93.5 million. The main equipment includes an autoclave, thickener, filter press, and rotary dryer. Financial analysis shows the project is feasible with a Payback Period of 4.85 years, an IRR of 19% above the MARR of 15%, and a positive NPV of 14.03 million at a discount of 19%. The sensitivity test showed that the project remained viable despite increased operational costs, so it was considered technically and financially prospective to support Indonesia's nickel downstreaming.